Estimation of mechanical properties of rock using artiﬁcial intelligence (2011)
This article presents the way two artificial intelligence techniques, neural networks and genetic algorithms were combined, for the development of a computational tool used to estimate mechanical properties such as tensile strength, uniaxial compression resistance and resistance to triaxial compression in sandstones, from petrophysical properties using test data from the Rock Mechanics Laboratory of the Colombian Petroleum Institute - Ecopetrol SA as training data facilitating the design of non-destructive tests with a certain degree of confidence and leading to cost reduction.